A Comparative Study on Effectiveness of Online and Offline Learning in Higher Education - Singh, Padmalini; Sinha, Rupesh; Koay, Wei Lun; Teoh, Kok Ban; Nayak, Prajna; Lim, Chung Hong; Dubey, Avinas Kumar; Das, Abhijit; Faturrahman, Iqbal; Aryani, Dwi Nita (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
The objective of the study is to assess the effectiveness of online and offline learning through higher education. The sudden outbreak of Covid-19 in various part of the world in 2020 has severely affected the educational institutions in various countries. Students were affected in the way to accept the hybrid form of learning and also grasp the interest towards the classes that were conducted online. The study aims to investigate the effectiveness of online and offline education in higher education. The study was carried out in India, Indonesia, Malaysia and other countries with 100 respondents among which major responses were from the youth population studying in Bachelor’s program, Diploma and Master’s mostly. The findings indicated that the effectiveness of online education is dismal, as students find it difficult to adjust to the online mode of education and the offline mode of education remains the most preferred mode of education.